Reflective Practice of Occupational Health Nursing During Covid-19 Pandemic: A Document Review - Isak Jurun Hans Tukayo; Syaifoel Hardy; Ridha Afzal; Akhir Fahruddin; Martha Debora Korompis; Mahmood Abdulrahman Al Jaidah (YCMM, 2022)
The Delta variant of Covid-19 is not yet completely extinct, the world is again shocked by of the new variant of Omicron, which have impact on the Occupational Health Nursing (OHN) practice. This study aims to analyze the reflection on the practice of OHN during the Covid-19 period and provide solution on the problems. This study used the document review method and PRISMA Analysis, supported by a quantitative descriptive design. The research was conducted through document search, keyword identification and article review from the Google Search Engine (n=169), Google Scholar (n=136), Research Gate (n=5), PubMed (n=10), Semantic Scholar (n= 80) and others (n=23), a total of 423 records. The three key words are reflective practice, occupational health nursing, and Covid-19. The supporting theory is Reflective Practice. The results of this study produced 8 documents that were worthy of review and 100% fulfilled the 6 key elements of OHN reflective practice, namely reflection, clinical situation or experience, promoting factors, hindering factors, and outcomes). This study recommended the need for a review of standard operating procedures of OHN related to continuing education, vaccines, safety, clinical aspects and the threat of shortage of OHNs in the midst of a pandemic.